(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
prostatic cancer is a malignant neoplasm characterized by elevated level 7-8 folds in both mRNA and protein levels during tumorigenesis of the prostate. Also, HER2/neu expression could be detected in prostatic intraepithelial neoplasia (PIN) ,It affects androgen receptor function and the progression of prostatic cancer and thedetermination of Association between HER2/neu and α-methylacyl coemzyme A racemase (AMACR) overexpressions in prostatic cancer as prognostic factors. This study included 50 patients aged from 50- < 70 years and 10 healthy men as control group matched with patient group ages. Then, paraffin-embedding procedure was prepared on tissues biopsy and then, hematoxylin and eosin staining (H. and E. staining) procedure was done . Finally, immunohistochemical procedure is done on both control cases and prostate cancer blocks. This immunohistochemical procedure detects her2/neu and AMACR overexpression according to DAKO protocol scoring system. The study showed that there is no significant difference in ages (P >0.05) between prostatic cancer patient and control group (68.46±6.26 years , 62.79±8.68 years) respectively and the prostatic cancer is more prevalence in ages >69 years old which represent 56% of cases. Also, the overexpression of AMACR represent weak positive (46%), moderate positive (34%), strong (20%) overexpressions. While, the overexpression of HER2/neu gives weak positive (60%), strong positive (40%) and the death occurred to 50% of prostatic cancer patient that have strong positive HER2/neu overexpression. Those whose ages are more than 69 years old who have liability for prostatic cancer . Immunohistochemical overexpressions of α-methylacyl coemzyme A racemase enzyme and HER2/neu have prognostic marker for prostatic cancer .